Enhancing Clinical Trial Efficiency: A Review Of Current Practices And Future Approaches - Sravanthi, Ammapalli; Prasad, P. Dharani (Journal of Neonatal Surgery, 2025)
Clinical trials are the cornerstone of modern medical research, serving as the definitive method for evaluating the safety, efficacy, and effectiveness of new therapeutic interventions. They play an essential role in approving and subsequent use of pharmaceuticals, medical devices, and other healthcare innovations. However, clinical trials are often resource-intensive, time-consuming, and subject to significant challenges that hinder their efficiency and overall success. These challenges include issues such as lengthy patient recruitment processes, high operational costs, complex regulatory requirements, and the significant burden of data management. As the healthcare and pharmaceutical industries strive to address these inefficiencies, there has been a growing shift toward enhancing clinical trial efficiency through the adoption of innovative methodologies, advanced technologies, and novel trial designs. This review explores the current practices in clinical trials, providing a comprehensive overview of the traditional trial structure, patient recruitment and retention methods, data management strategies, and regulatory compliance. It highlights the challenges that have long plagued clinical trials, including slow recruitment, high attrition rates, and logistical complexities in data handling. Additionally, the paper delves into current trends aimed at improving the efficiency of clinical trials, such as adaptive trial designs, the application of artificial intelligence (AI) and machine learning (ML), decentralized clinical trials (DCTs), and the use of wearable devices for remote monitoring. These innovations are paving the way for more flexible, faster, and cost-effective trials by leveraging technology to streamline processes and enhance participant engagement. Furthermore, the review examines future approaches that hold the potential to further enhance clinical trial efficiency. Key areas discussed include the integration of blockchain for data security and integrity, the growth of global trial networks for multinational collaboration, and the shift toward patient-centered trial designs that prioritize the needs and preferences of participants. These advancements aim to optimize trial operations, reduce costs, and ultimately bring new treatments to market more quickly and effectively. By synthesizing the current practices and emerging trends, this paper provides a comprehensive outlook on how clinical trials can evolve to meet the growing demand for faster, more efficient, and patient-centered research. The future of clinical trials lies in harnessing technology, collaboration, and innovative methodologies to streamline the entire process—from patient recruitment to data collection and analysis—ultimately improving the quality of research and accelerating the development of novel treatments